Lewisian turning point in the Chinese economy : comparison with East Asian countries - Minami, Ryoshin; Makino, Fumio; Kim, Kwan S; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2014)
This volume is concerned with labor market developments in China from a comparative perspective on selected East and South Asian countries. It closely examines the changing structure of China's labor market in the context of the Lewisisan turning point in ecomomic development.
Keywords: Economic development -- China; Economic development -- East Asia; China -- Economic conditions; East Asia -- Economic conditions